2017
DOI: 10.31729/jnma.3265
|View full text |Cite
|
Sign up to set email alerts
|

Clinicohematological Study of Pancytopenia in a Tertiary Care Hospital of Western Region of Nepal

Abstract: Introduction: Pancytopenia is a relatively common hematological entity and is a manifestation of many illnesses which can be life threatening at times. The severity of pancytopenia and the underlying pathology determine the management and prognosis. This study was conducted to evaluate hematological and bone marrow findings in patients presenting with pancytopenia. Methods: It was a prospective study carried out in Department of Pathology, Manipal College of Medical Sciences, Pokhara, Nepal, during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Ghartimagar et al found that patients' age ranged from 2 to 82 years with a mean age of 43.95 years, and there was male predominance. [5] Mansuri et al found that age of the patients ranged from 1 to 70 years with a slight male predominance. Most common age group was 11-20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghartimagar et al found that patients' age ranged from 2 to 82 years with a mean age of 43.95 years, and there was male predominance. [5] Mansuri et al found that age of the patients ranged from 1 to 70 years with a slight male predominance. Most common age group was 11-20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Ghartimagar et al found that most of the patients presented with generalized weakness, pallor, dypnoea and fever. [5] Mansuri et al found that most of the patients presented with generalized weakness and fever. The commonest physical finding was pallor, followed by splenomegaly and hepatomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…In present study we had 2 patients of Rheumatoid arthritis 1 of scleroderma who were on immunosuppressant, Azathioprine presenting with pancytopenia.1pt of chronic myeloid leukemia on Imatinib, he recovered after withdrawal of drug and referred to haemato-oncologist for further management. 4 1989 France 213 Malignant myeloid and lymphoid disorders Varma et al 15 1992 India 203 Aplastic anemia Tilak et al 5 1999 India 77 Megaloblastic anemia Kumar et al 16 2001 India 166 Aplastic anemia Khunger et al 6 2002 India 200 Megaloblastic anemia Memon et al 17 2008 Pakistan 230 Aplastic anemia Jha et al 19 2008 Nepal 148 Hypoplastic marrow Santra G et al, Das Bk et al 18 2010 Calcutta, India 111 Aplastic anemia Jain Naniwadekar 14 2013 India 250 Hypersplenism Ridhi Agarwal et al 13 2015Meerut, India 70 Malaria Iqbal W et al 7 2001 Pakistan 208 Megaloblastic anemia Monika et al 10 2016 India 169 Megaloblastic anemia Ghartimagar et al 20 2017 Nepal 138 Hypoplasia of marrow All these patients7 (13%) underwent marrow analysis and were found to have hypocellular marrow as shown in (Table 5). Bone marrow biopsy analysis also helped to cirrhosis of liver portal hypertension splenomegaly did not undergo marrow analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Jha A et al, Ghartimagar D et al, reported Hypoplasia of marrow as the leading cause while in present study 13%patient had hypocellular marrow. 19,20 This variation could be due to local food preferences, poverty, prevalence of infections, geographical location, climate season. Various causes cited in different studies is presented below in a tabulated form.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causes of pancytopenia show a wide variation throughout the world, and there is a need for local knowledge of the causes of this condition. [12345678910] The studies of pancytopenia from Uttarakhand, a north Himalayan state of India, are limited. In addition to clinical importance, the studies from this region may also vary from the rest of India due to geographical variation and, thus, may have epidemiological importance.…”
Section: Introductionmentioning
confidence: 99%